Mobilizing justice in sociolegal research: a mixed methods meta-analysis. - Portillo, Shannon; Sexton, Lori; Smith, Sarah M.; Dinsmore, Renee; Reyes, Erika Garcia (Crime, Law & Social Change, 2022)
Justice as a concept has permeated sociolegal scholarship in the U.S. since the founding of Law and Society as a field in the mid 1960s. Much of this scholarship has focused on theoretically driven areas of justice, and here we consider empirically how such concepts have been mobilized in prominent law and society journals from their inception through 2014. Based on a meta-analysis of 438 articles from Law & Society Review, Law & Social Inquiry, and Law & Policy, we present a typology of the forms of justice represented in sociolegal scholarship and describe how justice concepts are used and to what ends. We find that the justice ideas presented and how they are conceptualized and operationalized is highly contextualized and perspectival, and the perspectives represented are limited. We reflect on these findings and the first fifty years of sociolegal research in the U.S. and offer suggestions for the future.